Heat equation analysis using parallel programming tools / Emilia Mohamad Shukree - Mohamad Shukree, Emilia (2007)
Many new technologies, in terms of software and hardware had been introduced that had made computing power doubles every year. Programmers and software developers had introduced more high quality software’s, vivid and clear animations, more real time simulations, and any other programs that need more powerful processing. Sequential processing and computing is a thing of the past and cannot afford to today's software’s and programs that has the quality as mentioned earlier. That's what had made parallel computing and processing is the choice in the world of today. However, due to cost constrains, some organizations could not afford to have today's parallel supercomputers. Hence, urging developers and programmers to come up with a solution which is to virtualize the use of parallel processing which is why the Parallel Virtual Machine had come out as of today, to benefit organizations by connecting a few personal computers (PC’s) via today’s standard networking architectures. This research project is conducted to find the time difference between the parallel heat equation program that was built by the author derived from the former parallel coding by using C language and the modified sequential heat equation program in peer-to-peer (P2P) network and star topology network. SSH communications standard via RSA key will be used between those PC’s in both network architecture to ensure that the PVM daemons on those PC’s can be contacted and making sure that the PVM run smoothly. It is expected that the parallel heat equation programming will execute faster than the latter sequential heat programming code.